Preparation and application of terbium-doped titanium carbide quantum dots

By using terbium-doped titanium carbide quantum dots as fluorescent probes, the time-consuming and complex problems of ciprofloxacin detection in the prior art are solved, and the rapid and simple quantitative detection of ciprofloxacin in aqueous solution is achieved, and good biological Compatibility and industrial application prospects.

CN119463872APending Publication Date: 2025-02-18JIANGSU UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411606718.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ciprofloxacin detection method in water has the disadvantages of expensive instruments, complex sample extraction and pretreatment processes, and long time-consuming, making it difficult to achieve fast and simple quantitative detection.

Method used

Using terbium-doped titanium carbide quantum dots (Tb@Ti3C2 QDs) as fluorescent probes, Ti3C2 QDs were prepared by microwave method and mixed with terbium ions to construct a fluorescent probe for detecting ciprofloxacin, and use its specific identification. Ciprofloxacin, quantitative detection is achieved.

Benefits of technology

It realizes rapid and simple quantitative detection of ciprofloxacin in aqueous solution, has good biocompatibility and industrial application prospects, and avoids complex sample extraction and pretreatment processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463872A_ABST
    Figure CN119463872A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of terbium-doped titanium carbide quantum dots. The preparation comprises the following steps: mixing Ti3C2MXene with an alcohol solvent, heating for reaction, centrifuging a reaction product, and taking supernatant to obtain a Ti3C2QDs solution; dissolving water-soluble terbium salt and EDTA in water to obtain a terbium ion solution; and uniformly mixing the terbium ion solution with the Ti3C2QDs solution to obtain the terbium-doped titanium carbide quantum dots. According to the invention, the prepared Ti3C2QDs and terbium ions (Tb < 3 + >) are mixed to construct the terbium-doped Ti3C2QDs ratiometric fluorescent probe for detecting ciprofloxacin. Based on the characteristics of good biocompatibility, low toxicity, hydrophilicity and the like of the Ti3C2QDs and the specific recognition effect of the Tb-doped Ti3C2QDs on the ciprofloxacin, the invention develops a method for rapidly and simply detecting the ciprofloxacin, so that the quantitative detection of the ciprofloxacin in an aqueous solution sample is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of a fluorescent probe, and in particular to the preparation and application of terbium-doped titanium carbide quantum dots. Background Art

[0002] Ciprofloxacin is a commonly used fluoroquinolone antibiotic and is widely used in animal husbandry and medical industries. In recent years, the detection rate and concentration of ciprofloxacin in water bodies have gradually increased. Studies have shown that antibiotics in the environment can increase bacterial resistance, affect the balance of the ecosystem, and endanger human health. Therefore, the pollution problem of ciprofloxacin in water bodies needs to be solved urgently.

[0003] At present, the detection methods for antibiotics that are prone to drug resistance in water bodies include high-performance liquid chromatography, liquid chromatography-mass spectrometry, gas chromatography-mass spectrometry, microbial detection, spectrophotometry, etc., but the instruments used in these methods generally have disadvantages such as expensive instruments, complex sample extraction and pretreatment processes, and long time consumption. As a common trace detection technology, fluorescence analysis has the advantages of high sensitivity, low cost, simple operation, and rapidity, and is widely used in the detection of environmental pollutants.

[0004] Ti3C2 quantum dots (Ti3C2 QDs) prepared with Ti3C2 MXene as a precursor have small size and strong fluorescence properties. At the same time, rare earth fluorescent probes have the advantages of good fluorescence performance, large Stokes shift and long fluorescence lifetime, which can effectively reduce the interference caused by short fluorescence lifetime. Due to the simple operation, high sensitivity, short time consumption, wide linear range and low detection limit of this method, it has application potential in the detection of ciprofloxacin.

[0005] In order to detect quinolone antibiotics, Chinese patent CN118325117A discloses a terbium coordinated covalent organic framework fluorescent material and its preparation method and application. The fluorescent material is Tb 3+ The ions are loaded onto a covalent organic framework material, and the covalent organic framework material is used to improve the Tb-based 3+ The sensitivity and selectivity of fluorescent probes for the detection of quinolone antibiotics in food are improved. 3+ The fluorescent probe can be used for the detection of quinolone antibiotics, but the detection function depends on the covalent organic framework material and only relies on Tb 3+ The luminescence properties themselves cannot be used for the detection of antibiotics. When preparing fluorescent probes, once the covalent organic framework material is replaced, the selectivity and quantitative detection performance of the fluorescent probes are difficult to predict.

[0006] Chinese patent CN114392762A discloses a composite material based on a two-dimensional MXene nanostructure and a preparation method thereof. The present invention discloses a composite material based on a two-dimensional MXene nanostructure and a preparation method thereof, which belongs to the technical field of composite photocatalytic material preparation. The composite material is obtained by compounding nitrogen-doped Ti3C2MXene nanoparticles and rare earth element-doped g-C3N4; firstly, the Al atomic layer in Ti3AlC2 is etched with HF acid solution to obtain Ti3C2 MXene layered nanoparticles, and then heat-treated with a nitrogen-containing precursor to obtain nitrogen-doped Ti3C2 MXene material; using a nitrogen-containing precursor and a nitrate solution of a rare earth metal as reactants, calcining to obtain rare earth element-doped g-C3N4; finally, the nitrogen-doped Ti3C2 MXene nanoparticles and the rare earth element-doped g-C3N4 are mixed and calcined to obtain a composite material. In this invention, rare earth elements such as yttrium, lanthanum or cerium are doped in Ti3C2 Mxene to exert the synergistic effect of adsorption and photocatalysis, thereby improving the photocatalytic degradation ability of the composite material. However, the invention does not disclose that the composite material can be used for the quantitative detection of ciprofloxacin. In addition, the preparation method is complicated, requiring the Ti3C2 Mxene to be nitrogen-doped in advance and the rare earth elements to be loaded with g-C3N4, and then mixed and calcined. The preparation conditions are harsh and it is difficult to apply on a large scale. Summary of the invention

[0007] Purpose of the invention: The purpose of the present invention is to provide a method for preparing terbium-doped titanium carbide quantum dots, so as to solve the problem of how to prepare terbium-doped titanium carbide quantum dots. Another purpose of the present invention is to propose the application of terbium-doped titanium carbide quantum dots in the detection of ciprofloxacin, so as to solve the problem of how to quantitatively detect ciprofloxacin in aqueous solution.

[0008] Technical solution: The method for preparing terbium-doped titanium carbide quantum dots described in the present invention comprises the following steps:

[0009] (1) Ti3C2 MXene is mixed with an alcohol solvent and heated to react, and the reaction product is centrifuged to obtain a supernatant to obtain a Ti3C2 QDs solution;

[0010] (2) dissolving a water-soluble terbium salt and EDTA in water to obtain a terbium ion solution;

[0011] (3) The terbium ion solution and the Ti3C2 QDs solution are mixed to obtain terbium-doped titanium carbide quantum dots.

[0012] The present invention uses titanium carbide MXene as a precursor and adopts a microwave method to prepare Ti3C2 QDs. The prepared Ti3C2 QDs are mixed with a certain proportion of terbium ions (Tb 3+) were mixed to construct a terbium-doped Ti3C2 QDs ratiometric fluorescent probe (Tb@Ti3C2 QDs) for the detection of ciprofloxacin.

[0013] Preferably, in step (1), the alcohol solvent is at least one of ethylene glycol, propylene glycol and butylene glycol.

[0014] Preferably, in step (1), the material-liquid ratio of Ti3C2 MXene to alcohol solvent is 0.01-0.1 g: 5-15 mL.

[0015] Preferably, in step (1), the heating reaction condition is to react at medium heat in a microwave digestion tank for 15-45 minutes.

[0016] Preferably, in step (2), the water-soluble terbium salt is at least one of TbCl3, Tb(NO3)3, and Tb2(SO4)3.

[0017] Preferably, in step (2), the mass ratio of the water-soluble terbium salt to EDTA is 1-3:1-3, and the concentration of the water-soluble terbium salt in the terbium ion solution is 5-25 mM.

[0018] Preferably, in step (3), the volume ratio of the terbium ion solution to the Ti3C2 QDs solution is 1:1-3, and the conditions for mixing the terbium ion solution and the Ti3C2 QDs solution are: mixing the terbium ion solution and the Ti3C2 QDs solution at a pH of 7.0-11.0 and a temperature of 20-80°C.

[0019] Another aspect of the present invention discloses the application of terbium-doped titanium carbide quantum dots prepared by the preparation method in the detection of ciprofloxacin.

[0020] Specifically, the above application includes the following steps:

[0021] (1) mixing terbium-doped titanium carbide quantum dots and a ciprofloxacin aqueous solution and adjusting the pH to neutral to obtain a test solution;

[0022] (2) Exciting the test solution at an excitation wavelength of 366 nm, detecting the fluorescence intensity at emission wavelengths of 460 nm and 540 nm, and calculating the ratio of the fluorescence intensity at 460 nm to that at 540 nm;

[0023] (3) Determine the fluorescence intensity ratio at different ciprofloxacin concentrations, obtain a linear relationship between the ratio and the ciprofloxacin concentration, and calculate the ciprofloxacin concentration in the test solution based on the linear relationship and the fluorescence intensity ratio of the test solution.

[0024] Preferably, in step (1), the concentration range of the ciprofloxacin aqueous solution is 0-400 μmol / L, and the volume ratio of terbium-doped titanium carbide quantum dots to the ciprofloxacin aqueous solution is 1-5:1.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0026] The present invention develops a rapid and simple method for detecting ciprofloxacin based on the properties of Ti3C2 QDs such as good biocompatibility, low toxicity and hydrophilicity, and the specific recognition of ciprofloxacin by Tb-doped Ti3C2 QDs, thereby realizing the quantitative detection of ciprofloxacin in aqueous solution samples. The preparation method of the present invention is simple, and the preparation can be completed by simple mixing at room temperature, the reaction conditions are mild, and no complex and harsh precipitation and sintering steps are required, and it has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Transmission electron microscope image of Tb@Ti3C2 QDs;

[0028] Figure 2 XRD pattern of Tb@Ti3C2 QDs;

[0029] Figure 3 is the infrared spectrum of Tb@Ti3C2 QDs;

[0030] Figure 4 is the linear relationship between ciprofloxacin concentration and fluorescence intensity;

[0031] Figure 5 Tb 3+ Effect of concentration on the preparation of Tb@Ti3C2 QDs;

[0032] Figure 6 The effect of temperature on the preparation of Tb@Ti3C2 QDs;

[0033] Figure 7 The effect of pH on the preparation of Tb@Ti3C2 QDs. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0035] Example 1: A method for preparing terbium-doped titanium carbide quantum dots is as follows:

[0036] (1) Take 20 mL of 40% HF aqueous solution, stir it in an ice-water bath for 10 min, weigh 1 g of Ti3AlC2 and add it to the HF aqueous solution in small amounts several times. After it is completely added, stir it at 40°C for 24 h. After the reaction is completed, the precipitate is repeatedly centrifuged and washed until the pH is 6.0, and then vacuum dried at 80°C for 12 h. The obtained product is Ti3C2 MXene.

[0037] (2) 0.05 g Ti3C2 MXene was ultrasonically mixed with 10 mL ethylene glycol solution for 30 min, adjusted to pH 8.0, transferred to a polytetrafluoroethylene microwave digestion tank, reacted at medium heat for 30 min, cooled, centrifuged at 11000 r / min for 5 min, and the supernatant was collected to obtain a Ti3C2 QDs solution.

[0038] (3) EDTA and TbCl3·6H2O are weighed in a mass ratio of 1:1, and the EDTA and TbCl3·6H2O are dissolved in water to obtain a terbium ion solution, wherein the concentration of TbCl3 in the terbium ion solution is 20 mM;

[0039] (4) Under the conditions of pH 9.0 and 20°C, the terbium ion solution and the Ti3C2 QDs solution were mixed at a volume ratio of 1:2 to obtain terbium-doped titanium carbide quantum dots Tb@Ti3C2 QDs. The Tb@Ti3C2 QDs were characterized by high-resolution transmission HRTEM, X-ray diffraction (XRD), and Fourier transform infrared spectroscopy. The results are as follows: Figure 1-3 As shown, it is inferred that the crystal structure is amorphous, the size is about 2nm, the structure is spherical, there are amino and carboxyl groups, and Tb elements are present.

[0040] The terbium-doped titanium carbide quantum dots prepared by the above method are used to detect ciprofloxacin in aqueous solution, and the method is as follows:

[0041] (1) Terbium-doped titanium carbide quantum dots and ciprofloxacin aqueous solutions of different concentrations were mixed at a volume ratio of 2:1, and then the pH was adjusted to 7.0 to obtain a test solution; the concentration of the ciprofloxacin aqueous solution ranged from 0 to 400 μmol / L.

[0042] (2) Exciting the test solution at an excitation wavelength of 366 nm, detecting the fluorescence intensity at emission wavelengths of 460 nm and 540 nm, and calculating the ratio of the fluorescence intensity at 460 nm to that at 540 nm;

[0043] (3) Determine the fluorescence intensity ratio at different ciprofloxacin concentrations in the range of 0-400 μM to obtain a linear relationship between the ratio and the ciprofloxacin concentration. The results are as follows: Figure 4 The concentration of ciprofloxacin in the test solution is calculated based on the linear relationship and the fluorescence intensity ratio of the test solution.

[0044] Example 2: A method for preparing terbium-doped titanium carbide quantum dots is as follows:

[0045] (1) Take 20 mL of 40% HF aqueous solution, stir it in an ice-water bath for 10 min, weigh 1 g of Ti3AlC2 and add it to the HF aqueous solution in small amounts several times. After it is completely added, stir it at 40°C for 24 h. After the reaction is completed, the precipitate is repeatedly centrifuged and washed until the pH is 6.0, and then vacuum dried at 80°C for 12 h. The obtained product is Ti3C2 MXene.

[0046] (2) 0.01 g Ti3C2 MXene was ultrasonically mixed with 5 mL propylene glycol solution for 30 min, adjusted to pH 8.0, transferred to a polytetrafluoroethylene microwave digestion tank, reacted at medium heat for 15 min, cooled, centrifuged at 11000 r / min for 5 min, and the supernatant was collected to obtain a Ti3C2 QDs solution.

[0047] (3) EDTA and Tb(NO3)3 are weighed in a mass ratio of 3:1, and the EDTA and Tb(NO3)3 are dissolved in water to obtain a terbium ion solution, wherein the concentration of Tb(NO3)3 in the terbium ion solution is 25 mM;

[0048] (4) Under the conditions of pH 7.0 and 80°C, the terbium ion solution and the Ti3C2 QDs solution were mixed in a volume ratio of 1:1 to obtain terbium-doped titanium carbide quantum dots.

[0049] The terbium-doped titanium carbide quantum dots prepared by the above method are used to detect ciprofloxacin in aqueous solution, and the method is as follows:

[0050] (1) Terbium-doped titanium carbide quantum dots and ciprofloxacin aqueous solutions of different concentrations were mixed at a volume ratio of 1:1, and then the pH was adjusted to 7.0 to obtain a test solution; the concentration of the ciprofloxacin aqueous solution ranged from 0 to 400 μmol / L.

[0051] (2) Exciting the test solution at an excitation wavelength of 366 nm, detecting the fluorescence intensity at emission wavelengths of 460 nm and 540 nm, and calculating the ratio of the fluorescence intensity at 460 nm to that at 540 nm;

[0052] (3) Determine the fluorescence intensity ratio under different ciprofloxacin concentrations and obtain the linear relationship between the ratio and the ciprofloxacin concentration (y=0.0059x+1.3974, R 2 =0.9961), and the concentration of ciprofloxacin in the test solution was calculated based on the linear relationship and the fluorescence intensity ratio of the test solution.

[0053] Example 3: A method for preparing terbium-doped titanium carbide quantum dots is as follows:

[0054] (1) Take 20 mL of 40% HF aqueous solution, stir it in an ice-water bath for 10 min, weigh 1 g of Ti3AlC2 and add it to the HF aqueous solution in small amounts several times. After it is completely added, stir it at 40°C for 24 h. After the reaction is completed, the precipitate is repeatedly centrifuged and washed until the pH is 6.0, and then vacuum dried at 80°C for 12 h. The obtained product is Ti3C2 MXene.

[0055] (2) 0.1 g Ti3C2 MXene was ultrasonically mixed with 15 mL propylene glycol solution for 30 min, adjusted to pH 8.0, transferred to a polytetrafluoroethylene microwave digestion tank, reacted at medium heat for 45 min, cooled, centrifuged at 11000 r / min for 5 min, and the supernatant was collected to obtain a Ti3C2 QDs solution.

[0056] (3) EDTA and Tb2(SO4)3 are weighed in a mass ratio of 1:3, and the EDTA and Tb2(SO4)3 are dissolved in water to obtain a terbium ion solution, wherein the concentration of Tb2(SO4)3 in the terbium ion solution is 10 mM;

[0057] (4) Under the conditions of pH 11.0 and 40°C, the terbium ion solution and the Ti3C2 QDs solution were mixed in a volume ratio of 5:1 to obtain terbium-doped titanium carbide quantum dots.

[0058] The terbium-doped titanium carbide quantum dots prepared by the above method are used to detect ciprofloxacin in aqueous solution, and the method is as follows:

[0059] (1) Terbium-doped titanium carbide quantum dots and ciprofloxacin aqueous solutions of different concentrations were mixed at a volume ratio of 3:1, and then the pH was adjusted to 7.0 to obtain a test solution; the concentration of the ciprofloxacin aqueous solution ranged from 0 to 400 μmol / L.

[0060] (2) Exciting the test solution at an excitation wavelength of 366 nm, detecting the fluorescence intensity at emission wavelengths of 460 nm and 540 nm, and calculating the ratio of the fluorescence intensity at 460 nm to that at 540 nm;

[0061] (3) Determine the fluorescence intensity ratio under different ciprofloxacin concentrations, and obtain the linear relationship between the ratio and the ciprofloxacin concentration (y=0.0044x+1.7811, R 2 =0.9983), and the concentration of ciprofloxacin in the test solution was calculated based on the linear relationship and the fluorescence intensity ratio of the test solution.

[0062] Example 4: Investigating the effect of terbium ion solution concentration on the fluorescence intensity of terbium-doped titanium carbide quantum dots, the method is as follows:

[0063] The rest are the same as in Example 1, except that:

[0064] Terbium ion solutions were prepared at TbCl3 concentrations of 5mM, 10mM, 15mM, 20mM, 25mM, and 30mM, respectively, and reacted under the same temperature, incubation time, and pH conditions to detect their fluorescence intensity. The results are as follows Figure 5 As shown, when the concentration of terbium solution is 20mM, the fluorescence intensity changes significantly, and the characteristic peak of terbium appears at 540nm. Therefore, the experiment is carried out by doping 20mM terbium ion solution with quantum dot solution.

[0065] Example 5: The effect of the mixing temperature of the terbium ion solution and the Ti3C2 QDs solution on the fluorescence intensity of terbium-doped titanium carbide quantum dots was investigated as follows:

[0066] The rest are the same as in Example 1, except that:

[0067] The terbium ion solution and the Ti3C2 QDs solution were mixed at 20℃, 40℃, 60℃, and 80℃ to prepare different terbium-doped titanium carbide quantum dots, and the fluorescence intensity of the terbium-doped titanium carbide quantum dots was detected respectively. The results are shown in Figure 6 As shown, Figure 6 The solution reacted at 20°C showed a higher fluorescence intensity, with a more prominent characteristic peak at 540 nm.

[0068] Example 6: Investigating the effect of pH when the terbium ion solution and the Ti3C2 QDs solution are mixed on the fluorescence intensity of terbium-doped titanium carbide quantum dots, the method is as follows:

[0069] The rest are the same as in Example 1, except that:

[0070] Prepare a terbium ion aqueous solution with a TbCl3 concentration of 50 mM;

[0071] 0.665 mL of terbium ion aqueous solution was mixed with 3.335 mL of Ti3C2 QDs solution, and then adjusted with hydrochloric acid and ammonia buffer solution to 5 mL. The pH of the solution was adjusted to 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, and 12.0, respectively, and the fluorescence intensity was detected. The experimental results are shown in Figure 2. Figure 7 As shown, under the condition of pH 9.0, the fluorescence intensity of terbium-doped titanium carbide quantum dots is relatively high, and the characteristic peak of terbium at 540nm has a good peak shape.

[0072] Comparative Example 1: The rest is the same as Example 1, except that:

[0073] Replace TbCl3 with LaCl3.

[0074] Lanthanum-doped titanium carbide quantum dots were used to detect ciprofloxacin in aqueous solution, and an attempt was made to establish a linear relationship between the fluorescence intensity ratio at 460nm and 540nm and the concentration of ciprofloxacin. The results are as follows:

[0075] The statistical results show that the R 2 The value is 0.78893, and this linear relationship cannot be used to calculate the concentration of ciprofloxacin, that is, lanthanum-doped titanium carbide quantum dots cannot be used to detect ciprofloxacin in aqueous solution.

[0076] Comparative Example 2: The rest is the same as Example 1, except that:

[0077] Ciprofloxacin was replaced with ofloxacin.

[0078] The statistical results show that the R value of the linear relationship after fitting 2 The value is 0.89239, and this linear relationship cannot be used to calculate the concentration of ofloxacin. The terbium-doped titanium carbide quantum dots prepared in the present invention cannot be used to detect ofloxacin in aqueous solution.

[0079] Comparative Example 3: The rest is the same as Example 1, except that:

[0080] Ciprofloxacin was replaced with norfloxacin.

[0081] The statistical results show that the R value of the linear relationship after fitting 2 The value is 0.82153, and the linear relationship cannot be used to calculate the concentration of norfloxacin. The terbium-doped titanium carbide quantum dots prepared in the present invention cannot be used to detect norfloxacin in aqueous solution.

[0082] Comparative Example 4: The rest is the same as Example 1, except that:

[0083] Ciprofloxacin was replaced with metronidazole.

[0084] The statistical results show that the R value of the linear relationship after fitting 2 The value is 0.75214, and this linear relationship cannot be used to calculate the concentration of metronidazole. The terbium-doped titanium carbide quantum dots prepared in the present invention cannot be used to detect metronidazole in aqueous solution.

[0085] Comparative Examples 2-4 show that the terbium-doped titanium carbide quantum dots prepared in the present invention can only be specifically used for the detection of ciprofloxacin aqueous solution, and cannot be used for the quantitative detection of other antibiotics.

Claims

1. A method for preparing terbium-doped titanium carbide quantum dots, characterized in that: The following steps are included: (1) Ti3C2 MXene is mixed with an alcohol solvent and heated to react, and the reaction product is centrifuged to obtain a supernatant to obtain a Ti3C2 QDs solution; (2) dissolving a water-soluble terbium salt and EDTA in water to obtain a terbium ion solution; (3) The terbium ion solution and the Ti3C2 QDs solution are mixed to obtain terbium-doped titanium carbide quantum dots.

2. The method for preparing terbium-doped titanium carbide quantum dots according to claim 1, characterized in that: In step (1), the alcohol solvent is at least one of ethylene glycol, propylene glycol and butylene glycol.

3. The method for preparing terbium-doped titanium carbide quantum dots according to claim 1, characterized in that: In step (1), the material-liquid ratio of Ti3C2 MXene to alcohol solvent is 0.01-0.1 g: 5-15 mL.

4. The method for preparing terbium-doped titanium carbide quantum dots according to claim 1, characterized in that: In step (1), the heating reaction condition is to react at medium heat in a microwave digestion vessel for 15-45 minutes.

5. The method for preparing terbium-doped titanium carbide quantum dots according to claim 1, characterized in that: In step (2), the water-soluble terbium salt is at least one of TbCl3, Tb(NO3)3, and Tb2(SO4)3.

6. The method for preparing terbium-doped titanium carbide quantum dots according to claim 1, characterized in that: In step (2), the mass ratio of the water-soluble terbium salt to EDTA is 1-3:1-3, and the concentration of the water-soluble terbium salt in the terbium ion solution is 5-25 mM.

7. The method for preparing terbium-doped titanium carbide quantum dots according to claim 1, characterized in that: In step (3), the volume ratio of the terbium ion solution to the Ti3C2 QDs solution is 1:1-3, and the conditions for mixing the terbium ion solution and the Ti3C2 QDs solution are: mixing the terbium ion solution and the Ti3C2 QDs solution at a pH of 7.0-11.0 and a temperature of 20-80°C.

8. Use of terbium-doped titanium carbide quantum dots prepared according to the preparation method according to any one of claims 1 to 7 in the detection of ciprofloxacin.

9. The use according to claim 8, characterized in that: The steps include: (1) mixing terbium-doped titanium carbide quantum dots and a ciprofloxacin aqueous solution and adjusting the pH to neutral to obtain a test solution; (2) Exciting the test solution at an excitation wavelength of 366 nm, detecting the fluorescence intensity at emission wavelengths of 460 nm and 540 nm, and calculating the ratio of the fluorescence intensity at 460 nm to that at 540 nm; (3) Determine the fluorescence intensity ratio at different ciprofloxacin concentrations, obtain a linear relationship between the ratio and the ciprofloxacin concentration, and calculate the ciprofloxacin concentration in the test solution based on the linear relationship and the fluorescence intensity ratio of the test solution.

10. The use according to claim 9, characterized in that: In step (1), the concentration range of the ciprofloxacin aqueous solution is 0-400 μmol / L, and the volume ratio of terbium-doped titanium carbide quantum dots to the ciprofloxacin aqueous solution is 1-5:1.

Citation Information

Patent Citations

  • Composite material based on two-dimensional MXene nanostructure and preparation method thereof

    CN114392762A

  • Terbium coordination covalent organic framework fluorescent material as well as preparation method and application thereof

    CN118325117A